Management Event Katarsis Live Event Organizer di Pandemi Covid-19 dalam Event Virtual - Ahmad Muhawwin Daswar; Satya Indra Karsa (UNISBA Press, 2022)
Abstract. Drive in Twilight is an event to watch a cinema from inside the car that is shown through a projector and a large screen that has been set in such a way that it resembles a “tantap screen.” Drive in Senja was first held in August 2020, where the Covid-19 pandemic was also hitting Indonesia. Drive in Senja is only held in a few special cities, such as Jakarta and Bandung. The films shown by Drive in Senja come in various genres, from horror, action, to animation. Researchers have a goal for the form of planning, design, coordination, packaging, implementation and evaluation of the event so that it remains interesting and unique even though it is carried out in a virtual form, besides that the author also wants to know the reasons for making an event with such a concept, who are the targets of the event being held , knowing how to promote the event, how to socialize the event, and the goals the Catharsis Live team wants to achieve through the Drive in Twilight event. Researchers use the Goldbatt Model as a supporter of the results of this study. Researchers used qualitative research methods with a case study approach. Data collection techniques using interviews, observation, documentation, and literature study. The data analysis technique used belongs to Miles and Huberman. The results of the study show that Drive in Senja plans plans A and plan B as well as team coordination, ticket sales, payment methods are all digitally adapted to the Covid-19 pandemic. Abstrak. Drive in Senja adalah acara menonton bioskop dari dalam mobil yang ditayangkan melalui proyektor dan layar besar yang telah diatur sedemikian rupa sehingga menyerupai “layar tantap”. Drive in Senja pertama kali diadakan pada Agustus 2020, di mana pandemi Covid-19 juga melanda Indonesia. Drive in Senja hanya diadakan di beberapa kota khusus, seperti Jakarta dan Bandung. Film-film yang diputar oleh Drive in Senja hadir dalam berbagai genre, mulai dari horor, aksi, hingga animasi. Peneliti mempunyai tujuan berupa perencanaan, perancangan, koordinasi, pengemasan, pelaksanaan dan evaluasi acara agar tetap menarik dan unik walaupun dilakukan dalam bentuk virtual, selain itu penulis juga ingin mengetahui alasannya untuk membuat acara dengan konsep seperti itu, siapa target acara yang diadakan, mengetahui cara mempromosikan acara, cara mensosialisasikan acara, dan tujuan yang ingin dicapai tim Katarsis Live melalui acara Drive in Senja. Peneliti menggunakan Model Goldbatt sebagai pendukung hasil penelitian ini. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi dan studi kepustakaan. Teknik analisis data yang digunakan adalah Analisis Miles dan Huberman. Hasil kajian menunjukkan jika Drive in Senja mempersiapkan plan A dan plan B serta koordinasi tim, penjualan tiket, metode pembayaran semuanya secara digital disesuaikan dengan kondisi pandemi Covid-19.